Legal Certainty of Intercontinental Traditional Health Workers in Indonesia - Prastyo, Anggodo Rahayu; Yudiman, Twody; Lany, Arman (Research Horizon, 2025)
Intercontinental traditional health workers are health workers with a scientific basis in traditional Chinese health who perform traditional health services in Indonesia accordance with Health Law No. 17 of 2023. This research aims to conduct an in-depth study of the legal certainty of Intercontinental traditional health workers in Indonesia in relation to rights, authorities and sanctions in the provision of health services and support for National Health Network (JKN) benefits through the Health Social Security Organizing Agency (BPJS). The research is a qualitative research based on normative law in the form of a legal research process that focuses on legal rules or principles sourced from laws and regulations, court decisions, and doctrines from legal experts. The results of the study state that Intercontinental traditional health workers get legal certainty in accordance with the Law and Regulation of the Minister of Health as traditional health workers with authority and can practice in independent practices, community health centers, hospitals, traditional health service facilities and/or health service facilities (Griya Sehat). Intercontinental traditional health workers have not yet received benefit support from the National Health Network through the Social Security Organizing Agency. It is necessary to make regulations for Intercontinental traditional health practitioners that include internationally recognized competency standards, national registration and licensing mechanisms, and residency and work requirements